Coronavirus as the Possible Causative Agent of the 1889–1894 Pandemic - Anton Erkoreka; Josu Hernando-Pérez; Juan Ayllon (Infectious Disease Reports, 2022)
Using new and original nineteenth-century sources, we analysed the epidemiology, clinical features and virology of the 1889 pandemic, which was referred to at the time as ‘Russian flu’ or ‘Asiatic flu’. However, we rejected this identification of the disease as an ‘influenza’, which we believe to have been based on insufficient knowledge of the causative agent and instead posit that the pandemic was caused by a coronavirus. We provide a new account of the 1889–1893 pandemic, with a more detailed chronology that included at least four epidemiological waves. At the end of 1889, a new virus appeared in Europe, which could be identified as the coronavirus HCoV-OC43, causing crude death rates of 1.3 per 1000 population in St Petersburg; 2.1 per 1000 in Paris; 2.8 per 1000 in Bilbao and on the French–Spanish border; between 2.9 and 5.2 per 1000 in small towns in the Basque Country; and 5.8 deaths per 1000 in Madrid, which had the highest death rate. The clinical features of the disease differed from classical influenza pandemics in terms of the latency phase, duration, symptomatology, convalescence, immunity, age and death rates. Another factor to be considered was the neurotropic capacity of the disease. The most frequent form of the 1889 pandemic was the ‘nervous form’, with specific symptoms such as ‘heavy headache’ (céphalalgie gravative), tiredness, fever and delirium. There are strong parallels between the 1889–1894 pandemic and the COVID-19 pandemic, and a better understanding of the former may therefore help us to better manage the latter.